Exchange Rate Volatility and Capital Inflows in Developing Economies - Ejaz, Muhammad; Shahzad, Muhammad; Khan, Rana Ejaz Ali (Asian Development Policy Review, 2021)
The developing economies require inflow of capital for their economic development. The current study attempts to estimate that to what extent the capital inflows are influenced by exchange rate and volatility in exchange rate in the developing economies. Generalized Method of Moment (GMM) is applied on panel data-set of 34 developing countries for the years 1978-2015. The GARCH model is employed to measure volatility in exchange rate while capital inflows are captured by net foreign direct investment (FDI) and foreign portfolio investment (FPI). The findings explain that when the capital inflows are measured by FDI it is positively affected by exchange rate and negatively by volatility in exchange rate. The GDP growth has shown positive while terms of trade and interest rate have shown negative effect on capital inflows. The inflation has negative but negligible effect on FDI inflow. When the capital inflows are measured by FPI the results depicts that exchange rate, volatility in exchange rate and terms of trade have negative effect on FPI. The economic growth, interest rate and industrialization have shown positive effect on capital inflows captured by FPI. The volatility in exchange rate has shown negative effect on capital inflows (measured by FDI as well as FPI) so exchange rate fluctuations should be minimized in order to enhance the capital inflows in developing economies.